Abbott & Costello. The complete Universal Pictures collection. [Discs 9-10] [videorecording (DVD)] - Barton, Charles, 1902-1981; Abbott, Bud, 1897-1974; Costello, Lou; Main, Marjorie, 1890-1975; Cleveland, George, 1885-1957; Ching, William, 1913-1989; Lugosi, Bela, 1882-1956; Karloff, Boris, 1887-1969 (Universal Studios Home Entertainment, 2008)
The wistful widow of Wagon Gap: Falsely accused of murder, Lou is forced to take care of a widow and her six children. Abbott and Costello meet Frankenstein: Bud and Lou encounter Frankenstein's monster, Dracula and the Wolf man. Mexican hayride: Bud and Lou head south of the border after getting mixed up in a phony oil stock scam. Abbott and Costello meet the killer, Boris Karloff: Bud and Lou meet up with Boris Karloff after a guest is murdered at their hotel.